Standardized Concept Design of Structural Testing and Camber of Railway Flat Wagons - hary soebagyo; Arief Riyadi T. K (Magister Teknik Mesin Universitas Pancasila, 2026)
The train is a means of mass transportation that functions to transport people and goods. The level of train safety must be maintained during operation, especially the structural parts which must be strong and reliable in accepting the loads they carry following RAMS provisions (Reliability, Availability, Maintainability, Safety). The main structural part of concern is the lower frame of the train carriage whose main function is to support all the loads received. The design of the lower frame structure is made in such a way that it is slightly curved so that there is a pre-stress load that can withstand bending loads when the structure is loaded. This slightly curved structural design is called